The value of alumni networks in responding to the public administration theory and practice: Evidence from the COVID-19 pandemic in China. Issue 4 (1st October 2020) - Ding, Fangda; Riccucci, Norma M.
Abstract: There has been a good deal of research on the role of nongovernmental organizations in addressing public concerns and issues. However, alumni networks, mainly regarded as a platform for in-group benefits between alumni and their alma maters, have attracted little attention in terms of their potential utility to the broader public. But the unexpected vital role of alumni networks in addressing the recent novel coronavirus (COVID-19) in China provides some insights into the value of alumni networks in both the practice and theory of public administration. Along with the successful practice in China, this essay attempts to understand how alumni networks can be used to assist in shared struggles in general, helping to solve major public challenges in practice in contexts beyond China, and to extend the understanding of alumni networks as potential areas of study through existing theoretical frameworks in public administration (e.g., collaborative governance and nonprofit organizations). The essay also provides directions for a future research agenda on the value of alumni networks for public administration.